ANTIOXIDANT AND WOUND HEALING PROPERTIES OF SOME SELECTED NEPALESE PLANTS (International Journal of Food and Nutritional Sciences, 2022)
Medicinal plants are significant sources of bioactive substances that need methodical investigation.The chemical variety of natural goods offers many opportunities for the development of novel drugs.The purpose of this research was to examine the biochemical characteristics of crude extracts from fifteen medicinal plants found in Nepal. Total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activity were assessed using a colorimetric method, and the antibacterial activities were investigated by measuring the minimum inhibitory concentrations (MIC) using the broth dilution method and the zone of inhibition (ZoI) using the agar well diffusion method. Out of all the plant extracts under study, the methanolic extracts from Eupoterium adenophorum and Acacia catechu had the greatest TFC (10.23 ± 1.07 mg QE/gm) and TPC (55.21 ± 11.09 mg GAE/gm). With an IC50 value of 1.3 μg/mL, Acacia catechu demonstrated excellent antioxidant activities. Myrica esculenta, Syzygium cumini, and Mangifera indica extracts were the next to demonstrate these characteristics. Morus australis demonstrated antibacterial activity against the following pathogens: methicillin-resistant Staphylococcus aureus (MRSA) (ZoI: 19 mm, MIC: 0.19 mg/mL), Pseudomonas aeruginosa (ZoI; 20 mm, MIC: 0.05 mg/mL), Staphylococcus aureus ATCC 25923 (ZoI: 22 mm, MIC: 0.012 mg/mL), and Klebsiella pneumoniae (ZoI: 25 mm, MIC: 0.012 mg/mL). Broad-spectrum antibacterial activity was shown by an extract from Morus australis, Eclipta prostrata, and Hypericum cordifolium. It is advised that future research look into the medicinal plants' secondary metabolites to find further clinical effectiveness.